2007
DOI: 10.1007/s11240-007-9269-5
|View full text |Cite
|
Sign up to set email alerts
|

Induction and comparison of different in vitro morphogenesis pathways using embryo of cumin (Cuminum cyminum L.) as a model material

Abstract: In this study, using cumin embryo as explant and manipulating plant growth regulators (PGRs) in regeneration medium, the main in vitro morphogenesis pathways including direct shoot organogenesis, direct somatic embryogenesis, indirect somatic embryogenesis, and indirect shoot organogenesis were obtained. The effects of PGRs, subculture, and light on the induction and progression of different pathways were studied in detail. Direct shoot organogenesis occurred on the meristematic zone, while direct somatic embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Rapid regeneration is a procedure with low incidence of undesirable somaclonal variation. A lot of minor genes and environmental factors affect regeneration through callus [ 24 ]. In contrast, direct regenerations are more stable, simple and needs less time to regenerate a large number of plants with low incidence of somaclonal variation and chromosomal abnormalities [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid regeneration is a procedure with low incidence of undesirable somaclonal variation. A lot of minor genes and environmental factors affect regeneration through callus [ 24 ]. In contrast, direct regenerations are more stable, simple and needs less time to regenerate a large number of plants with low incidence of somaclonal variation and chromosomal abnormalities [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Presence of many types of responses were observed on explant, especially embryo, and have been reported. Ebrahimie et al [ 24 ] reported both direct shoot organogenesis and somatic embryogenesis on the embryo explants of Cuminum cyminum . Direct shoot organogenesis occurred on the meristematic zone, while direct somatic embryogenesis was observed on the hypocotyl part of the embryo.…”
Section: Resultsmentioning
confidence: 99%
“…Sharifi (1995) used hypocotyl and cotyledon as an explant in cumin tissue culture and Tawfik andNoga (2001, 2002) used hypocotyls, internodal stem and leaflet for regeneration. Ebrahimie et al (2003Ebrahimie et al ( , 2006Ebrahimie et al ( , 2007 used embryos as explant and obtained large number of shoots without any intermediated callus formation and sub culturing. Our objective is to establish a convenient method of genetic transformation in cumin, therefore we have selected cumin embryos as explant for genetic transformation using biological constraint independent biolistic gene gun method.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported both somatic and zygotic embryos of 8-10 mm long to be optimal for SSE induction, whereas those reaching 12-14 mm were incapable for SSE formation. Somatic embryogenesis and caulogenesis can occur simultaneously within the same explant (Budimir 2003;Ebrahimie et al 2007), or can be completely separated (Ebrahimie et al 2007). Morphogenic responses can also be modified by managing culture conditions, such as sucrose and PGR content in the culture media (Charrière and Hahne 1998).…”
mentioning
confidence: 99%